Application of Constructivism Method in Islamic Religious Education for Development Skills Think Critical and Religious Student - Afi Parnawi; Tri Gunawan; Farid Naya; Alwiyah, Alwiyah (Cita konsultindo, 2025)
Study This aiming For explore implementation theory Study constructivist in Islamic Religious Education (PAI) as well analyze How approach This push active and reflective learning . Learning theory constructivist focuses on learning based on experience , interaction social , and reflection , allowing student For build knowledge they in a way independent . The research method used is approach qualitative with design studies case . Data collected through interview deep with PAI teachers, students , and principals school , observation class , and analysis document learning like Plan Learning Implementation (RPP) and teaching modules . Research results show that PAI teachers implement various learning strategies constructivist , including learning based on problem -based learning, discussion group , learning based on projects , and usage technology interactive . Implementation of this strategy proven increase involvement active students , develop skills think critical , and facilitate deep reflection related implementation Islamic teachings in life daily .